DER, Operating Leverage, and Financial Stability in Indonesian Banks (2020–2024) : A Correlation Analysis - rio rio (Jurnal Maps (Manajemen Perbankan Syariah), 2026)
Banking financial stability is a multidimensional issue that underpins the resilience of Indonesia’s financial system, particularly in a dual-banking landscape where Islamic and conventional banks are exposed to similar macro-financial shocks but may exhibit distinct risk dynamics shaped by Shariah-compliant intermediation, contract structures, and depositors’ return expectations. This study aims to examine the relationship between the Debt-to-Equity Ratio (DER), Operating Leverage (OL), and banking financial stability, measured using the Stability of the Financial System ratio (SRFS) in Indonesia. A quantitative approach is applied using Spearman’s rank correlation, as one variable (OL) fails to satisfy normality based on the Shapiro–Wilk test. Secondary data are obtained from annual reports and official statistics published by Bank Indonesia for the 2020–2024 period. Descriptive results indicate mean values of 99.48 for DER, 1.392 for OL, and 0.134 for SRFS, with fluctuations reflecting notable financial dynamics over the observation period. The findings suggest that DER tends to increase, potentially elevating financial risk, while the relatively stable OL indicates consistent operational efficiency. However, variations in SRFS point to the banking system’s vulnerability to external pressures. This study offers implications for regulators and industry stakeholders in designing risk-mitigation policies, strengthening capitalization, and enhancing resilience supervision to support the stability of the national banking sector, including the advancement of financial stability research in Islamic banking in Indonesia.